Education On Recycling Paper Waste Into Seed Paper As An Environmentally Friendly Product For Vocational School Students - Yoesti Arianti; Rosita Dewati (Universitas Veteran Bangun Nusantara, 2025)
Paper is a material with various daily applications, as a medium for writing, printing, drawing, wrapping, etc. Although in the digital era the role of paper is increasingly minimal, it cannot be denied that the use of paper continues. Besides being useful, paper also leaves a problematic side when it becomes waste. Paper waste that is tried to be eliminated by burning will cause air pollution in the form of disturbing and dangerous smelling smoke, especially in large and continuous volumes. Recycling paper waste is important in order to prevent and minimize environmental damage due to inappropriate handling. The process of recycling paper aims to process paper waste into